ANALISIS KUALITAS WEBSITE DENGAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS - Ihsan, Azzam Afdhalul; Hidayati, Ulfah; Mardinawati, Mardinawati (KEUNIS, 2022)
This study aims to analyze the quality of the Tokopedia website based on user perceptions using the WebQual 4.0 method. It is also meant to find out the gap between the level of performance and the level of user interest and indicators that are the main priority for improvement based on Importance Performance Analysis (IPA). The dimensions used in WebQual 4.0 consist of usability, information quality, and interaction quality. The sample in this study was 100 respondents using the Tokopedia website. Based on the results of research using WebQual 4.0, the website's quality has a WebQual Index score 0.85, which was good because it is close to 1,00. While based on Importance Performance Analysis, in quadrant one, four indicators need to improve their performance. The average value of the gap for each dimension is 0.24 gap for the usability dimension, -0.32 for the information quality dimension, and -0.32 for the interaction quality. The value of the most significant gap lies in the indicator that the Tokopedia Website guarantees the security of users' personal data information of -0.72, which means more attention and improvement should be given to the indicators with the most significant gap.